Broken Narrative The Politics of Contemporary Art in Albania - Mazzi, Marco (punctum books, 2022)
Broken Narrative provides an extensive reflection on history, politics, and contemporary art, revolving around the cornerstones of the artistic practice of Albanian artist Armando Lulaj. The core of the book is formed by and extended interview of Lulaj by Italian artist and writer Marco Mazzi. This inquiry starts in the year 1997, a year of social and political upheaval in Albania, of anarchy, controversies and emigration, of toxic seeds of neoliberalism sprouting in an already wounded country, and continues to the present day, where politics, hidden behind art forms, has practically destroyed (again) every different and possible future of the country. This book also sketches out a connection between the recent Albanian political context and contemporary art by considering the realities of Albania as essential for an understanding of the dynamics of international power in contemporary art and architecture, and the role of politics therein. Broken Narrative comes in a bilingual English-Japanese edition, in part as homage to the subtle esthetics of Japanese poetry, which has inspired many of the Lulaj's works, while equally evoking the subversive films of the Red Army, active in Japan at the turn of the 1960s and '70s. Broken Narrative contains a double preface in English by Albanian scholar Jonida Gashi and in Japanese by photographer Osamu Kanemura.